Historical growth in total factor carbon productivity of the Chinese industry – A comprehensive analysis. (1st January 2018) - Li, Wenwen; Wang, Wenping; Wang, Yu; Ali, Mustafa
Abstract: In this study we used the metafrontier function to analyze carbon dioxide emissions in relation to environmental production technology in China. We, comprehensively, estimated and decomposed total factor carbon productivity in 36 sectors of Chinese industry in the years between 2003 and 2015. Moreover, industry differences and dynamic evolution of total factor carbon productivity were analyzed in order to reveal sources of growth in total factor carbon productivity. The industrial sectors were classified into four groups according to the dual criteria of carbon emissions and technology. The results are as follows: (1) From 2003 to 2015, the total factor carbon productivity of industry in China increased by 5.93%. During 2004 and 2009, extensive expansion of heavy industry caused decline in total factor carbon productivity. After 2010, the transformation of economic development patterns and the substantial increase in green investment have led to a rapid increase in total factor carbon productivity in China. (2) The difference in total factor carbon productivity among sectors is significant. Low-carbon and high-technology industry is the technology leader. (3) Decomposition analysis reveals that technology innovation gradually plays a dominant role in total factor carbon productivity growth of China's industry. Technical efficiency of the high-carbon industries makes the total factor carbon productivity increase. The gap between the low-tech industry and the high-carbon industry with the metafrontier technology continues to expand.